Digipreneurship as an Effort to Strengthen The Digitalization of The Islamic Economy in Indonesia - Afif, Fayiz; Nabila, Dzakiyatun Nisa Nurun; Rohmah, Ria Marzuqotur (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2023)
The digitization of the Islamic economy in Indonesia offers opportunities to strengthen economic growth based on Islamic principles. Through the development of sharia e-commerce platforms, technology-based financial services, and sharia-based fintech innovations, this digitization facilitates easier and faster access to Islamic products and services. This research uses three theoretical approaches: digital economy theory, entrepreneurship theory, and Islamic economic theory, with the aim of understanding the contribution and impact of digipreneurship in strengthening the digitalization of the Islamic economy in Indonesia and analyzing the principles of Islamic economics that can be applied in digital business. The research method used is qualitative with a descriptive content analysis approach and phenomenological design. The results highlight the importance of digipreneurship as an effort to strengthen the digitalization of the Islamic economy in Indonesia and integrate the principles of Islamic entrepreneurship into digital businesses. Digitalization of the Islamic economy through digipreneurship opens opportunities for Muslim participation in the digital market, encourages innovation, and promotes inclusive economic growth. The integration of Islamic values and principles into the digital economy is important in the digital era in Indonesia. Digipreneurship serves as a means to harness the potential of digital technology by upholding Islamic values, so that individuals and businesses can play an important role in advancing the digitalization of the Islamic economy, driving economic growth, and creating a prosperous future.